O nowych sposobach zarządzania fizyczną różnicą na ekranie: autotematyzm i intencja zwrotna wobec reprezentacji „anormalnego” ciała w filmie - Cybulski, Adam (Zagadnienia Rodzajów Literackich, 2020)
The paper discusses particular modes of audiovisual self-consciousness in autothematic and highly (self )reflexive films, equipped with “empowered” devices of narration that question popular conventions of portraying physical otherness. Living in Oblivion (1995), Storytelling (2001), Jeremy the Dud (2017), and Chained for Life (2018) are analysed in contexts of lowering narrative illusion methods of managing “troublesome bodies” on screen, as well as the long tradition of “disabling” portrayals of visible dissimilarities (e.g. little person as oneiric figure, inspiring “supercrip” stereotype).